Kinerja Usaha Tanaman Anggrek Bulan (Phalaenopsis Amabilis) Pada PT Multi Agro Bali Di Desa Sembung Kecamatan Mengwi Kabupaten Badung - KADEK WINA CITRA WATI; I KETUT SUAMBA; IDA AYU LISTIA DEWI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2015)
ABSTRACT Kadek Wina Citra Wati. NIM 1005315066. The Month Orchid (Phalaenopsis Amabilis) of Bussinese Performance in PT Multi Agro Bali at Sembung Village Mengwi Badung. Guided by: Dr. Ir. I Ketut Suamba, MP. and Ida Ayu Listia Dewi, SP, MAgb. The PT Multi Agro Bali is one of the month orchid bussines since 1998. The performance of the business does not only focus on the economy aspect but also the non economy aspect. The combination of those two aspects can increase the busines performance. The purposes of the research are to describe the moon orchid. Business at PT Multi Agro Bali from the job description and the management performance. The other purpose is to know the business development from the production and also the profit development. The methods used for the research are the qualitative and quantitative descriptions. The result of the research shows that the month orchid business of PT Multi Agro Bali applies the job description and the function of the management are planning, organization, direction and the supervision. The development of the business shows high growing of two sides, they are the development with the lowest presentage 0,003% and the highest 1,238%. The lowest revenue development is 1,22% and the highest 12,49%. It is suggested that the company is that is better the business makes the accountant notes, to add and to enlarge the place capacity of the green house to accommodate more month orchid. Keywords: Performance, Business, Month Orchid, PT Multi Agro Bali.